Randomized controlled trials of acupuncture for the treatment of essential hypertension: a meta-analysis - Lu, Yuqing; Li, Lingjie; Wang, Zhaoqin; Huang, Yan; Zhong, Rui; Xu, Jing; Liu, Huirong; Wu, Huangan; Cheng, Ling; Wu, Luyi (Journal of acupuncture and tuina science, 2023)
Objective To systematically assess the efficacy and safety of acupuncture therapy for essential hypertension. Methods A computerized literature search of the Chinese National Knowledge Infrastructure (CNKI), Chongqing VIP Database (CQVIP), Wanfang Academic Journal Full-text Database (Wanfang), China Biology Medicine Disc (CBM), PubMed, EMBASE, and Cochrane Library was conducted to retrieve randomized controlled clinical trials on acupuncture as the main intervention for the treatment of essential hypertension published from the inception of the database to 30 January 2021. The risk-of-bias assessment was carried out for each included study according to the Cochrane Handbook. Data analysis was performed using Review Manager 5.4.1 and Stata 15.0. Results After the screening, 46 randomized controlled trials involving a total of 3 859 subjects were included. Primary outcomes included changes in the diastolic blood pressure after intervention [eight studies showed that the acupuncture plus antihypertensive drug group was better than the antihypertensive drug monotherapy group [mean difference (MD)=1.45, 95% confidence interval (CI) (0.48, 2.43), P =0.004, fixed effects model; I 2 =39%] and changes in the systolic blood pressure after intervention {11 studies showed that the acupuncture plus antihypertensive drug group was better than the antihypertensive drug monotherapy group [MD=8.60, 95%CI (7.12, 10.07), P <0.00001, fixed effects model; I 2 =26%]}. The secondary outcome was antihypertensive efficacy, 12 studies of acupuncture monotherapy group [risk ratio (RR)=1.20, 95%CI (1.12, 1.28), P <0.00001, fixed effects model; I 2 =36%] and 15 studies of acupuncture combined with antihypertensive drug group [RR=1.27, 95%CI (1.20, 1.34), P <0.00001, fixed effects model; I 2 =6%] showed better results than the antihypertensive drug monotherapy group in antihypertensive efficacy. In terms of the adverse events, four studies showed that the acupuncture monotherapy group had fewer adverse events than the antihypertensive drug monotherapy group [RR=0.10, 95%CI (0.04, 0.25), P <0.00001, fixed effects model; I 2 =0%]. Conclusion Acupuncture combined with antihypertensive drugs is superior to antihypertensive drugs alone in reducing blood pressure, and acupuncture therapy is effective and safe for the treatment of essential hypertension with fewer side effects. However, there is still a lack of high-quality multicenter randomized double-blinded controlled trials in this field. Rigorous large-sample clinical trials are needed to validate these findings.